Słowniki Bartłomieja z Bydgoszczy (1532 i 1544). Stan badań i perspektywy badawcze - Jankowiak, Lucyna Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2017)
The purpose of this article is to recall the 16th century Latin-Polish dictionaries by Bartholomew of Bydgoszcz. The article describes the figure of the monk, the history of his works as well as their structure and contents. The interest in the lexicons grew in the 70s of the 20th century when a manuscript dated 1532 (considered to be lost after the second world war) was found and a dictionary dated 1544 was unexpectedly discovered. A decision was made then to (jointly) publish both lexicons in the reversed version (Polish-Latin). This project still has not been completed which certainly has had its effect on the researchers’ weakening interest in the dictionaries and a small number of publications. Therefore the article presents possibilities of the analysis of the Polish and Latin lexical material.